La gestión del patrimonio bibliográfico en la Biblioteca de Catalunya: funciones, acciones y difusión - Altarriba Vigatà, Nuria (My University, 2026)
Después de una breve introducción a la evolución del concepto de patrimonio bibliográfico a lo largo de la historia, se describen las funciones del Catàleg Col·lectiu del Patrimoni Bibliogràfic de Catalunya. Se presenta la Biblioteca de Catalunya, máxima autoridad competente en materia de patrimonio bibliográfico en Cataluña, y se profundiza en sus funciones y actividades relacionadas con el incremento y la difusión del patrimonio bibliográfico. Finalmente se reflexiona sobre la actualidad y la transformación digital, las oportunidades que puede presentar la Inteligencia Artificial y el papel de las bibliotecas patrimoniales en este nuevo escenario.

This article begins with a brief overview of the evolution of the concept of bibliographic heritage over time, followed by a description of the functions of the Collective Catalog of Bibliographic Heritage of Catalonia. It then presents the Library of Catalonia, the principal authority overseeing bibliographic heritage in Catalonia, and examines its roles and activities in the preservation, enhancement, and dissemination of bibliographic collections. Finally, the discussion addresses the current digital transformation, explores the potential opportunities offered by Artificial Intelligence, and considers the evolving role of heritage libraries in this new landscape.
Managing Bibliographic Heritage at the Library of Catalonia: Roles, Iniciatives, and Dissemination
Keywords: Patrimonio bibliográfico; Bibliotecas patrimoniales; Digitalización